Tribological behavior in micro–sheet hydroforming. (May 2016) - Sato, Hideki; Manabe, Ken-ichi; Wei, Dongbin; Jiang, Zhengyi; Alexandrov, Sergei
Abstract: In this paper, the tribological behavior and its size effects in micro–hydromechanical deep drawing (MHDD) are theoretically and experimentally investigated. It is found that a required fluid pressure for hydrodynamic lubrication significantly increases with scaling down micro–scale due to a high sealablity at small relative punch diameter to minimum thickness. Moreover, the opposite tribological size effect from a conventional microforming appears in MHDD in which the fluid medium can be kept in open lubricant pockets (OLPs) by applying a fluid pressure and, the friction coefficient decreases as a specimen size decreases. Thus, MHDD can induce the hydrodynamic lubrication and lubrication in OLPs and improve the tribological behavior in microforming by applying the appropriate fluid pressure. Graphical abstract: Scale dependences of (a) normalized maximum friction forces and (b) average friction coefficients in flange area for different lubrication conditions in MDD and MHDD introduced in Eqs. (38 ) and(45 ). Highlights: We model a new friction model considering size effect in microsheet hydroforming. Required fluid pressure for hydrodynamic lubrication increases with scaling down. Fluid medium can be kept in open lubricant pockets by applying fluid pressure. Friction force can be reduced with scaling down in microsheet hydroforming. Tribological size effect is different between microsheet forming and hydroforming.